Time patterns of precautionary health behaviours during an easing phase of the COVID-19 pandemic in Europe - Anikó Bíró; Réka Branyiczki; Petér S. Elek (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Using data from the COVID-19 questionnaire of the Survey of Health, Ageing and Retirement in Europe (SHARE), we investigate the time patterns of precautionary health behaviours of individuals aged 50 and above during the summer of 2020, an easing phase of the COVID-19 pandemic in Europe. We also examine how these health behaviours differ by the presence of chronic conditions such as hypertension, high cholesterol level, heart disease, diabetes or chronic bronchitis, which can be considered as risk factors for COVID-19. Our results suggest that while on average, people became less precautious during our analysed time period, this is less so for those who are at higher risk. We also document large regional differences in precautionary health behaviours and show that higher risk individuals are on average more cautious in all regions. We conclude that people adjusted their health behaviours in line with the generally understood risk of the COVID-19 disease. At the same time, our results also point out divergences in the level of willingness to take different precautionary steps.
Keywords: I10; I12; I18; 330; COVID-19; health risk; precautionary behaviours; SHARE data